2013
DOI: 10.1021/jm300642a
|View full text |Cite
|
Sign up to set email alerts
|

A Nonionic Inhibitor with High Specificity for the UDP-Gal Donor Binding Site of Human Blood Group B Galactosyltransferase: Design, Synthesis, and Characterization

Abstract: 9-(5-O-α-D-galactopyranosyl)-D-arabinityl-1,3,7-trihydropurine-2,6,8-trione (1) was designed and synthesized as a nonionic inhibitor for the donor binding site of human blood group B galactosyltransferase (GTB). Enzymatic characterization showed 1 to be extremely specific, as the highly homologous human N-acetylgalactosaminyltransferase (GTA) is not inhibited. The binding epitope of 1 demonstrates a high involvement of the arabinityl linker, whereas the galactose residue is only making contact to the protein v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…This is time and resource intensive. [12] For the enzymatic reaction of GTB, the transfer of galactose from the donor substrate UDP-Gal onto an acceptor substrate results in the formation of UDP.B ecause UDP is an inhibitor of GTB, it must be re- . Our research group has shown that NMR spectroscopy is ap owerful tool for progress curve analysis; [25] we werea ble to determine inhibition constants for inhibitors of GTB from such experimentsb efore.…”
Section: Progress Curve Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…This is time and resource intensive. [12] For the enzymatic reaction of GTB, the transfer of galactose from the donor substrate UDP-Gal onto an acceptor substrate results in the formation of UDP.B ecause UDP is an inhibitor of GTB, it must be re- . Our research group has shown that NMR spectroscopy is ap owerful tool for progress curve analysis; [25] we werea ble to determine inhibition constants for inhibitors of GTB from such experimentsb efore.…”
Section: Progress Curve Analysismentioning
confidence: 99%
“…Our research group has shown that NMR spectroscopy is ap owerful tool for progress curve analysis; [25] we werea ble to determine inhibition constants for inhibitors of GTB from such experimentsb efore. This has previously been achieved by the use of alkaline phosphataseb yS chaefer et al [12] In contrast to the work by Schaefer et al,w ep erformed our inhibition studies at as lightly more acidic pD value of 5.8 in order to increase the solubility of the examined ligands and therefore substituted alkaline with acidic phosphatase from wheat germ. For the orientation of the core fragment (as shown in panel A), all three ligands show an identical binding mode.…”
Section: Progress Curve Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Schaefer et al 9,10 proposed that the ionic pyrophosphate group could be replaced by a nonionic group to increase bioavailability and facilitate penetration of cells and cell compartments to reach the target enzymes. This concept was first advanced to derive nonionic mimics of the sugar-nucleoside donor of the human blood group B galactosyltransferase.…”
mentioning
confidence: 99%